Resolvin E1 Regulates Th17 Function and T Cell Activation - Oner, Fatma; Alvarez, Carla; Yaghmoor, Wael; Stephens, Danielle; Hasturk, Hatice; Firatli, Erhan; Kantarci, Alpdogan (Frontiers in Immunology, 2021)
Resolvin E1 (RvE1) is a specialized pro-resolving lipid mediator derived from eicosapentanenoic acid and plays a critical role in the resolution of inflammation and tissue homeostasis. Th17 cells are a distinct group of T helper (Th) cells with tissue-destructive functions in autoimmune and chronic inflammatory diseases via the secretion of IL-17. Dendritic cell (DC)-mediated antigen presentation regulates the Th17-induced progression of inflammation and tissue destruction. In this study, we hypothesized that the RvE1 would restore homeostatic balance and inflammation by targeting the Th17 function. We designed three experiments to investigate the impact of RvE1 on different phases of Th17 response and the potential role of DCs: First CD4+ T cells were induced by IL-6/TGF to measure the effect of RvE1 on Th17 differentiation in an inflammatory milieu. Second, we measured the impact of RvE1 on DC-stimulated Th17 differentiation in a co-culture model. Third, we measured the effect of RvE1 on DC maturation. RvE1 blocked the CD25, RORt and CCR6 expression and IL-17, IL-21, IL-10 and IL-2 production suggesting inhibition of T cell activation, Th17 stimulation, and migration under Th17 polarizing conditions. In co-culture experiments, RvE1 prevented T cell activation through a decreased CD25 expression. RvE1 suppressed the activation of DCs by limiting their pro-inflammatory cytokine production. Collectively, our findings demonstrated that the RvE1 targeted the Th17 activation and the DC function as a potential mechanism for inflammatory resolution and acquired immune response.